2016
DOI: 10.3389/fimmu.2016.00095
|View full text |Cite
|
Sign up to set email alerts
|

Potential of PEGylated Toll-Like Receptor 7 Ligands for Controlling Inflammation and Functional Changes in Mouse Models of Asthma and Silicosis

Abstract: Prior investigations show that signaling activation through pattern recognition receptors can directly impact a number of inflammatory lung diseases. While toll-like receptor (TLR) 7 agonists have raised interest for their ability to inhibit allergen-induced pathological changes in experimental asthma conditions, the putative benefit of this treatment is limited by adverse effects. Our aim was to evaluate the therapeutic potential of two PEGylated purine-like compounds, TMX-302 and TMX-306, characterized by TL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 55 publications
0
7
0
Order By: Relevance
“…Existing evidence strongly suggests that in the lung, as well as in many other tissues, fibrosis is underlined by a complex multistep inflammatory response driven by a network of cytokines/chemokines, growth factors and signaling processes, often associated with leucocyte infiltration and fibroblast activation (20,21). In the murine model of silicosis used in this study, Swiss Webster was the mouse strain of choice as this is not an inbred mouse strain, thereby modeling the outbred human condition associated with clinical silicosis as previously reported (15,(22)(23)(24). The kinetics of leukocyte infiltration in BAL fluid revealed that there was a marked increase in the number of total leukocytes at 7 days, which reduced progressively with time.…”
Section: Discussionmentioning
confidence: 96%
“…Existing evidence strongly suggests that in the lung, as well as in many other tissues, fibrosis is underlined by a complex multistep inflammatory response driven by a network of cytokines/chemokines, growth factors and signaling processes, often associated with leucocyte infiltration and fibroblast activation (20,21). In the murine model of silicosis used in this study, Swiss Webster was the mouse strain of choice as this is not an inbred mouse strain, thereby modeling the outbred human condition associated with clinical silicosis as previously reported (15,(22)(23)(24). The kinetics of leukocyte infiltration in BAL fluid revealed that there was a marked increase in the number of total leukocytes at 7 days, which reduced progressively with time.…”
Section: Discussionmentioning
confidence: 96%
“…By releasing pro-inflammatory cytokines and chemokines, the inflammatory macrophages are also involved in inducing granuloma formation, which further overlaps with an extensive fibrotic response throughout the lung interstitial area ( Kawasaki, 2015 ). The characteristic features of human silicosis can be modeled in mice by intranasal instillation of crystalized silica particles ( Ferreira et al, 2013 , 2016 ; Trentin et al, 2015 ). LASSBio-897 (2 and 5 mg/kg), given orally from days 21–27 post-silica, significantly inhibited an extensive area of fibro-granulomatous formation, which reach about 40% of the lung parenchyma in non-treated mice 28 days post-challenge.…”
Section: Discussionmentioning
confidence: 99%
“…Murine IL-6, TNF-α, and macrophage inflammatory protein-2 (MIP-2/CXCL-2) levels were measured in right lung samples by means of ELISA kit (R&D Systems, Minneapolis, MN, United States) as previously described ( Ferreira et al, 2016 ). The results were expressed as picograms of cytokine per right lung.…”
Section: Methodsmentioning
confidence: 99%
“…8-hydroxyadenine derivatives.comparatively more effective and safer, deserving further investigations in drug development particularly for silicosis. This third generation is focused on developing candidates for treating autoimmune diseases[112].Zhu et al synthesized a novel 8-hydroxyadenine TLR7 agonist, SZU-101 (17,Fig. 9).…”
mentioning
confidence: 99%